(untitled) (Eurasian Research Bulletin, 2023)
This abstract presents an analysis of ways to improve the competitive environment in Uzbekistan through effective tax administration. The competitive environment plays a crucial role in promoting economic growth, attracting investments, and fostering entrepreneurship. The study focuses on exploring the potential of tax administration as a tool to create a favorable business climate and enhance competition. It examines various strategies and measures that can be implemented to improve tax administration practices and minimize barriers for businesses. The findings highlight the importance of simplifying tax procedures, reducing tax burdens, promoting transparency, and providing support and incentives for businesses. The proposed recommendations aim to enhance the competitive environment in Uzbekistan, attract domestic and foreign investments, and stimulate economic development